The Contribution of Single Leg Speed Hop and Hanumanasanam Exercises on Mawashi Geri's Kick Results in Male Athletes Dojo KKI Yapim Medan in 2021 - Imran Akhmad; Amirsyah Putra Lubis; Febiola Dimanjuntak (UNIVERSITAS NEGERI MAKASSAR, 2022)
This study aims to determine the contribution of single-leg speed hop and hanumanasana exercises to the mawashi Geri kick results for the male athlete of the KKI yapim Medan 2021 dojo. The method used in this research is an experimental method of experimentation. The population in this study amounted to 30 people. The sampling technique used is purposive sampling. The number of samples of athletes used was 14 people. This research was carried out for 8 weeks with a frequency of exercise 5 times every week. The results obtained from hypothesis testing indicate that: (1). The single-leg speed hop exercise contributed 58.3% to Mawashi Geri's Kick Results for the male athlete of the KKI dojo Yapim Medan 2021 (2). Hanumasana training contributed 40.1% to Mawashi Geri's Kick Results (3). There is a jointly significant contribution between Single leg speed hop and hanumanasana exercises on Mawashi Geri's kick results of 59.6%.